2018
DOI: 10.1080/09540121.2018.1428728
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological performance in patients with asymptomatic HIV-1 infection

Abstract: Human immunodeficiency virus (HIV-1) infection and acquired immunodeficiency syndrome (AIDS) lead to neurocognitive disorders; however, there is still much knowledge to be gained regarding HIV-associated neurocognitive disorders. The purpose of this study was to assess the cognitive performance, instrumental activities of daily living, depression, and anxiety in patients with asymptomatic HIV-1 infections compared with seronegative participants without neurocognitive impairment. We studied a sample consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…We recruited and clinically evaluated 60 individuals with asymptomatic HIV-1 Infection and an equal number of seronegative controls. These individuals correspond to those involved in a previous study by our group [39]. The inclusion criteria for individuals with HIV-1 Infection were (i) a diagnosis of HIV-1 Infection in the asymptomatic stage; (ii) age ranging between 18 and 58 y/o (to control any potential age-related cognitive immaturity or decline) [24]; (iii) the completion of at least two years of elementary school; (iv) a maximum time since HIV diagnosis of 9 years (considering nine years is the maximum period HIV-1 infected individuals can remain asymptomatic) [40]; and (v) no history of alcohol and/or drug use, neurological, neuropsychological, and/or psychopathological disorders before HIV-1 diagnosis.…”
Section: Subjectssupporting
confidence: 69%
See 1 more Smart Citation
“…We recruited and clinically evaluated 60 individuals with asymptomatic HIV-1 Infection and an equal number of seronegative controls. These individuals correspond to those involved in a previous study by our group [39]. The inclusion criteria for individuals with HIV-1 Infection were (i) a diagnosis of HIV-1 Infection in the asymptomatic stage; (ii) age ranging between 18 and 58 y/o (to control any potential age-related cognitive immaturity or decline) [24]; (iii) the completion of at least two years of elementary school; (iv) a maximum time since HIV diagnosis of 9 years (considering nine years is the maximum period HIV-1 infected individuals can remain asymptomatic) [40]; and (v) no history of alcohol and/or drug use, neurological, neuropsychological, and/or psychopathological disorders before HIV-1 diagnosis.…”
Section: Subjectssupporting
confidence: 69%
“…In this study, using ARPA, we assess the efficiency of a short version of a full neuropsychological protocol for HAND detection, recently proposed by our group [39]. We then compare it with other clinical screening instruments to define community-specific cut-off values for HAND diagnosis in individuals with asymptomatic HIV-1 Infection ascertained from a Caribbean community inhabiting Barranquilla, Colombia.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, our research group studies the differential expression of ncRNA in subjects with Alzheimer's disease compared to healthy subjects. We also plan to study the exosomal load in patients with attention deficit-hyperactivity disorder [359][360][361][362][363][364] and HIV and Huntington's disease [365,366]. Funding: This study was financed by MINCIENCIAS, project "Nuevos ARN no codificantes exosomales y su papel en la patogénesis de la Enfermedad de Alzheimer", code 121584468097, grant 844/2019, contract 416-2020, awarded to Grupo en Genética y Medicina Molecular and Grupo de Productividad y Competitividad, Universidad del Norte, Barranquilla, Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals living with HIV commonly demonstrate a neuropsychological pro le with prominent disturbances in executive functioning [1,2,3,4,5]. In addition to the cognitive impairment associated with HIV, there is a high rate of substance use disorders in the HIV population, making it di cult to determine which cognitive disturbances are due to HIV or illicit substances.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown similar performance on the Interference trial between HIV+ and HIVindividuals [2,15,16,17]. Others have found that individuals living with HIV perform signi cantly worse on the Interference trial than individuals who are HIV- [4,18,19]. Within the literature on cocaine dependence, there has been greater consistency in demonstrating di culties on the Interference trial and a higher number of response errors [11,20,21,22].…”
Section: Introductionmentioning
confidence: 99%